Male engineers: an interpretive phenomenological analysis of the experiences of persistence in higher education - Ecklund, Adam P., author; Kuk, Linda, advisor; Banning, James, committee member; Strathe, Marlene, committee member; Siller, Thomas, committee member (Colorado State University. Libraries, 2013)
More and more engineering programs have become concerned with retention and persistence in their degrees, because about half of their students either change majors or do not graduate at all (Center for Institutional Data Exchange and Analysis, 2000). Male students were chosen for this study because they make up 92.9% of all civil engineers, 90.6% of electrical and electronics engineers, and 90% of all aerospace engineers (National Committee on Pay Equity, 2008). Furthermore, this study was intended to discover factors to better understand how male undergraduate engineering students persisted in their program. While there is a plethora of research on retention and persistence, little qualitative research existed on the male engineering students' perspective of persistence and what factors students identified to assist them to remain in the program. The theoretical framework for this qualitative study was based on the institutional experiences within Tinto's (1993) Student Retention Model. The purpose of this study was to understand factors related to undergraduate engineering students persistence. The five research questions explored were: (1) what factors of the academic experience are helpful to male student persistence in engineering? (2) How does academic performance impact the student experience and their ability to persist in engineering? (3) What factors related to participation in social activities is helpful to male student persistence in engineering? (4) What features of faculty interactions are supportive to male student persistence in engineering? And, (5) what features of peer interactions are supportive to male student persistence in engineering? The research method for this study utilized the interpretative phenomenological analysis. The analysis consisted of twelve total interviews, seven senior and five junior students within the mechanical and electrical and computer departments, at a mid-size private institution, located in the southwest. This study suggested factors that aided in a student's persistence were preparation prior to college, developing a strong support network, and being grounded in academic skills and characteristics. Aspects of intrinsic and extrinsic motivation also assisted these students to persist. These twelve students further expressed their views to why peers left engineering and described certain factors that they felt needed to be tackled to increase persistence in engineering programs.
Keywords: persistence; male; retention; engineering; higher education